Pengaruh Ukuran Dimer Nanopartikel Bola Emas, Perak, dan Aluminium yang Ditambahkan pada Lapisan Back Surface terhadap Efisiensi Sel Surya CIGS - Abi Syaibah; Mulda Muldarisnur (Universitas Andalas, 2024)
This research aims to determine the effect of the size and material of spherical nanoparticle dimers placed on the back surface layer of CIGS solar cells on the resulting current density. This research was conducted computationally using the finite difference time domain (FDTD) method. Three materials were studied: silver, gold, and aluminium. For each material, nanoparticle diameter was varied. The calculation results show that the short circuit current density (Jsc) increases with the nanoparticle diameter. Silver nanoparticle dimers showed the highest increase in Jsc. A sphere diameter of 60 nm produces the highest Jsc. The increase in the Jsc of CIGS solar cells is due to the back reflection of light into the active layer of solar cells by nanoparticles and the near field excitation around nanoparticle dimers. The significant increase in Jsc shows the potential for utilizing silver nanoparticle dimers to increase the efficiency of CIGS solar cells.